Faktor – Faktor yang Mempengaruhi Financial Statement Fraud dengan Analisis Fraud Triangel (Studi Empiris Pada Perusahaan yang Terdaftar di JII Tahun 2016-2018) - Safitri, Trimas Adi; Hariyanto, Eko (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2022)
This study was conducted to analyze the effect of financial stability, external pressure, financial target, nature of industry and rasionalization on financial statement fraud. Sample used was 26 companies listed on the Jakarta Islamic Index (JII) in 3 years observation. The type of data used is secondary data. The data is in the form of annual report of companies listed on the Jakarta Islamic Index (JII) in 2016 – 2018. Hypothesis testing is conducted using logistic regression method with SPSS 23 software. This study was conducted using the Binary Logistic analysis method. The result showed that the variables of financial stability has a negative effect on financial statement fraud, external pressure and financial target has a positive effect on financial statement fraud. But this study does not prove the positive influence of the nature of industry and rasionalization variables. From those result it can be concluded that there are 2 variables that have positive effect, 1 variable that have negative effect, influence and 2 variables that do not have a positive effect on financial statement fraud.